An exploratory study of a conceptual framework for developing micro-credential courses in Malaysian higher education institutions / Fauziah Saadah Abdul Halim, Johan @ Eddy Luaran and Roslinda Alias - Abdul Halim, Fauziah Saadah; Luaran, Johan@Eddy; Alias, Roslinda (UiTM Press, 2022)
The rapid growth of technology and digitalization has led to a new model of learning known as micro-credential to reorient Higher Education Institutions and prepare graduates for work related skills in the 21st century. Even with much attention and support from the Malaysian Government, there is, however, still a lack of consensus for proper implementation of micro-credentials in Higher Education Institutions due to its infancy stage. Using grounded theory and qualitative content analysis, a conceptual framework was developed with three main themes emerging. These are; (1) learning principles, (2) e- learning theories and models and (3) assessment principles with reference to micro- credentials. The creation of this conceptual framework intends to help guide practitioners in the development of micro-credential courses in Higher Education Institutions in Malaysia.